2012
DOI: 10.2131/jts.37.463
|View full text |Cite
|
Sign up to set email alerts
|

No toxicological effects on acute and repeated oral gavage doses of single-wall or multi-wall carbon nanotube in rats

Abstract: -Three female Crl:CD(SD) rats/group were dosed with single wall carbon nanotube (SWCNT) or multi wall carbon nanotube (MWCNT) four times by gavage at a total of 50 mg/kg bw or 200 mg/kg bw (four equally divided doses at one-hour intervals). Acute oral doses of SWCNT and MWCNT caused neither death nor toxicological effects, and thus the oral LD 50 values for SWCNT and MWCNT were considered to be greater than 50 mg/kg bw and 200 mg/kg bw, in rats respectively. Five or ten Crl:CD(SD) rats/sex were dosed with SWCN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 23 publications
1
14
0
1
Order By: Relevance
“…Sharma et al, [10] showed that nanoparticles were mainly found to be retained in the liver after 14 day of sub-acute oral exposure to ZnO-NPs at a higher dose (300 mg/kg). However, Matsumoto et al, [33] suggested that repeated oral gavage of nanoparticles reached the gastro-intestinal tract as agglomerates and were mostly excreted via faeces but no investigations and results to support this suggestion were presented. Further characterization of nanoparticles in the gastrointestinal tract, including both absorption and excretion in response to ZnO-NPs intake are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Sharma et al, [10] showed that nanoparticles were mainly found to be retained in the liver after 14 day of sub-acute oral exposure to ZnO-NPs at a higher dose (300 mg/kg). However, Matsumoto et al, [33] suggested that repeated oral gavage of nanoparticles reached the gastro-intestinal tract as agglomerates and were mostly excreted via faeces but no investigations and results to support this suggestion were presented. Further characterization of nanoparticles in the gastrointestinal tract, including both absorption and excretion in response to ZnO-NPs intake are needed.…”
Section: Discussionmentioning
confidence: 99%
“…In regard to carbon-based NMs, there were no treatment-related effects in rats upon 28-day oral exposure to 12.5 mg/kg single-walled carbon nanotubes (SWCNTs; basic morphology sheet form consisting of entangled CNTs, diameter 2 nm) or 50 mg/kg multi-walled carbon nanotubes (MWCNTs; basic morphology entangled CNTs, diameter 30 nm; Matsumoto et al 2012). Nevertheless, Matsumoto et al conclude that, due to CNT absorption and persistence, longer-term effects of these materials cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…None of the tested nanomaterials cause local or systemic effects (Buesen et al, 2014). Similarly, studies performed by Matsumoto and co-workers did not reveal toxic effects after acute and repeated oral doses of single-or multi-wall carbon nanotubes (Matsumoto et al, 2012). The toxicity of MWCNTs is more adverse in the case of inhalation as compared to oral exposure.…”
Section: Mammalian Toxicity (Rodents)mentioning
confidence: 72%